Protein encoded by oncogene 6b from Agrobacterium tumefaciens has a reprogramming potential and histone chaperone-like activity - Ishibashi, Nanako; Kitakura, Saeko; Terakura, Shinji; Machida, Chiyoko; Machida, Yasunori (Frontiers in Plant Science, 2014)
Crown gall tumors are formed mainly by actions of a group of genes in the T-DNA that is transferred from Agrobacterium tumefaciens and integrated into the nuclear DNA of host plants. These genes encode enzymes for biosynthesis of auxin and cytokinin in plant cells. Gene 6b in the T-DNA affects tumor morphology and this gene alone is able to induce small tumors on certain plant species. In addition, unorganized calli are induced from leaf discs of tobacco that are incubated on phytohormone-free media; shooty teratomas and morphologically abnormal plants, which might be due to enhanced competence of cell division and meristematic states, are regenerated from the calli. Thus, the 6b gene appears to stimulate a reprogramming process in plants. To uncover mechanisms behind this process, various approaches including the yeast-two-hybrid system have been exploited and histone H3 was identified as one of the proteins that interact with 6b. It has been also demonstrated that 6b acts as a histone H3 chaperon in vitro and affects the expression of various genes related to cell division competence and the maintenance of meristematic states. We discuss current views on a role of 6b protein in tumorigenesis and reprogramming in plants.